POSTPARTUM CARE IN CENTRAL JAVA TRADITION - Ita Rahmawati (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: The puerperal period is a critical period. 60% of maternal deaths occur after delivery and 50% of them occur in the first 24 hours. The high rate of maternal and child mortality in Indonesia is closely related to social and cultural factors, particularly the Java community. During the postpartum, Abstinence / or postnatal care suggestion is usually associated with the physical condition of the recovery process. Aims: This study aims to determine postpartum care is based on the tradition of Central Java. Methods: This study is a combination of quantitative and qualitative study (Mixed Methods). The samples is 81 postpartum mothers. Data collection instrument was a structured questionnaire and indepth interview guidelines. Quantitative data with a frequency distribution. The results of qualitative data in narrative form. Results: Postpartum care based on the traditions of Central Java obtained: (1) 96.3% Capital postpartum do massage after delivery, when the foot bed to be straightened out, and not allowed to leave the house for 40 days, (2) 95.1% Capital postpartum Wearing pilis, ( 3) Wear stagen (88.9%), (4) There should be a nap (84%), (5) Do not eat eggs, meat, shrimp, fish (82.7%), (6) When themorning shower should to be shampoo (60.5%), and (7) Always drink herbal medicine (59.3%). Conclusion: The majority of postpartum care is based on the tradition of Central Java is still detrimental to the health of postpartum mothers so that they can affect the recovery process in the post-partum period.